The FIT therapy for the treatment of musculoskeletal and neurological disorders related symptoms: A retrospective observational study - Palmieri, Beniamino; Vadalà, Maria; Laurino, Carmen (Asian Journal of Medical Sciences, 2019)
Background: Far Infrared Waves (FIW) with frequency range among few hundreds gigahertz (GHz) and few terahertz (THz) display some positive effects on neurological and musculoskeletal disorders. Aims and Objectives: Our retrospective observational study describes the benefits observed by the administration of an infrared –trapping and focusing plaster (FIT-PATCH) in patients affected by different musculoskeletal and neurological symptoms. Materials and Methods: 100 patients were retrospectively reviewed through the Second Opinion Medical Network. Each patient sticked a FIT-PATCH every 5 days for 1 month upon the skin in the painful/inflamed area. Quality of life (QOL) assessment was evaluated by the Short Form-36 (SF-36) health survey questionnaire before starting the treatment and after the fourth week and the Visual Analogue Scale (VAS) completed the pre-post treatment subjective pain record. Results: SF-36 showed significantly improvement of the pre-post treatment scores (P < 0.03), pain score (P < 0.02), general health score (P < 0.03) and in the emotional component scores (P < 0.03). The VAS pain score was either improved (P < 0.02) after plaster administration. No side effects or allergenic skin reactions were reported along the study. Conclusions: The FIT patches improved the symptoms probably through a mechanism involving the sebaceous/sweat glands system spreading the fit irradiating infrared THz waves energy, to the surrounding tissues with both a thermal and electromagnetic putative effect.The occlusive mechanism of the patch on the skin surface increasing the local thermic gradient cannot be adequately supposed to be therapeutically effective, because the FIT patch locally applied induces haemodynamic microvascular modification, not only locally but also remote. Thus, the intrinsic chemical properties of the FIT formulation absorbs and concentrates the endogenous infrared waves amplifying and reverberating them into the underlying tissues near and far, through low-Q-factor helical antennas of the sweat glands spreading the energy all over the body. Hence, the claim is that fit basically absorbs and concentrates the endogenous infrared waves into the affected districts and accelerates symptoms recovery.